Multicultural Islam, Diversity of Qira'at And Its Implications for Istinbath Law - Khilmi, Akhmad Saifudin; Abd. Basid (Universitas Islam Malang, 2024)
One of the discussions of ulumul qur'an which has a very important position in the study of Islamic science is the Science of Qira'at. Qira'at Science is a scientific fan that concentrates on examining the validity of the text of the Qur'an, both in terms of pronunciation and writing. According to scientific terms, qira'at is one of the madhhabs (schools) of pronunciation of the Qur'anic recitation chosen by one imam qurro' as a school that is different from other schools. Differences in reading the Qur'an in general can affect changes in meaning, including the implications for legal istinbath. However, is the taking of Istinbath law from a madzhab adopted by a country in harmony with the qira'at that is popular in that country? This research is in the form of library research (literature study), literature study can be interpreted as a data collection technique by conducting a study of books, literature, notes, and reports that have a relationship with the problem being solved. The object of observation in the research is the diversity of qira'at and its implications for Istinbath law in a madzhab. After analysis, it was found that a recitation of qira'at that is popular in a country does not have to be in line with the method of Istinbath law carried out by the imam of the madzhab that applies in that country. The results of this research are expected to provide a new perspective in the study of Ulumul Qur'an as well as knowing the values that are an inspiration for the community.